Serum from patients with cirrhosis undergoing liver transplantation induces permeability in human pulmonary microvascular endothelial cells ex vivo - Bokoch, Michael P.; Xu, Fengyun; Govindaraju, Krishna; Lloyd, Elliot; Tsutsui, Kyle; Kothari, Rishi P.; Adelmann, Dieter; Joffre, Jérémie; Hellman, Judith (Frontiers in Medicine, 2024)
Introduction Patients with cirrhosis undergoing liver transplantation frequently exhibit systemic inflammation, coagulation derangements, and edema, indicating endothelial dysfunction. This syndrome may worsen after ischemia–reperfusion injury of the liver graft, coincident with organ dysfunction that worsens patient outcomes. Little is known about changes in endothelial permeability during liver transplantation. We hypothesized that sera from these patients would increase permeability in cultured human endothelial cells ex vivo. Methods Adults with cirrhosis presenting for liver transplantation provided consent for blood collection during surgery. Sera were prepared at five time points spanning the entire operation. The barrier function of human pulmonary microvascular endothelial cells in culture was assessed by transendothelial resistance measured using the ECIS ZΘ system. Confluent cells from two different endothelial cell donors were stimulated with human serum from liver transplant patients. Pooled serum from healthy men and purified inflammatory agonists served as controls. The permeability response to serum was quantified as the area under the normalized resistance curve. Responses were compared between time points and analyzed for associations with clinical characteristics of liver transplant patients and their grafts. Results Liver transplant sera from all time points during surgery-induced permeability in both endothelial cell lines. The magnitude of permeability change was heterogeneous between patients, and there were differences in the effects of sera on the two endothelial cell lines. In one of the cell lines, the severity of liver disease was associated with greater permeability at the start of surgery. In the same cell line, serum collected 15 min after liver reperfusion induced significantly more permeability as compared to that collected at the start of surgery. Early postreperfusion sera from patients undergoing living donor transplants induced more permeability than sera from deceased donor transplants. Sera from two exemplary cases of patients on preoperative dialysis, and one patient with an unexpectedly long warm ischemia time of the liver graft, induced exaggerated and prolonged endothelial permeability. Discussion Serum from patients with cirrhosis undergoing liver transplantation induces permeability of cultured human pulmonary microvascular endothelial cells. Increased endothelial permeability during liver transplantation may contribute to organ injury and present a target for future therapeutics.